Carmen Nestares's Venus en Buenos Aires: Neocolonialist Cyber-Romance, Virtual Lies, and the Transatlantic Queer - Maite Zubiaurre (Studies in 20th & 21st Century Literature, 2006)
Carmen Nestares's novel Venus en Buenos Aires (2001) chronicles a transatlantic lesbian love affair between a Spaniard and an Argentinean that begins in cyber-space and culminates in reality. At first, the novel reads "innocently" as an uncomplicated cyber-romance fiction, but once the romance becomes physical after the lovers meet on Latin American soil, certain unsettling elements arise. Online, the Spanish and Argentinean cultures, supposedly "united" by the same language, seem to intermingle easily and graciously, but offline, they are more conflicted, as the Spanish lover adopts a neocolonialist stance. From a distance she considers Argentina a land of capitalist promise and potential wealth, but once there she reveals a lack of comprehension of Argentine reality. Hence this article focuses on the disturbing semantics of neocolonialist politics that lurk beneath neo-utopian transatlantic Lesbos and its "pseudo-democratic" online rhetoric.
Keywords: Carmen Nestares; Venus en Buenos Aires; lesbian; love; love affair; cyber-space; cyber-romance fiction; neocolonialism; Argentinia; Spain; neo-utopian; transatlantic